Psikologi Komunikasi Sebagai Pendekatan Fase Adaptasi di Era Pasca Covid-19 - Mochammad Irfan Achfandhy; Budi Ariyanto (Universitas Terbuka, 2023)
The post-Covid-19 era is marked by all social activities having resumed. However, the new era poses problems for the students of Islamic boarding schools who have to re-adapt after a long period of studying at home (online). This research elaborates the re-adaptation phase and the communication approach implemented by the students of the Islamic boarding school. The research uses an explanatory qualitative method with a phenomenological approach. Sources of data were obtained from six students of the Thoriqul Huda Islamic Boarding School. The results showed that the re-adaptation phase included; honeymoon, crisis, recovery and adjustment. The adaptation phase is running again effectively by using a communication psychology approach in the recovery phase. Era pasca Covid-19 ditandai dengan seluruh kegiatan dan aktivitas sosial sudah berjalan kembali. Namun era baru menimbulkan permasalahan bagi santri pondok pesantren yang harus melakukan adaptasi kembali setelah lama belajar di rumah (online). Penelitian ini mengelaborasi fase adaptasi kembali dan pendekatan komunikasi yang di implementasikan santri pondok pesantren. Penelitian menggunakan metode kualitatif eksplanatif dengan pendekatan fenomenologi. Sumber data diperoleh dari enam santri Pondok Pesantren Thoriqul Huda. Hasil penelitian menunjukkan fase adaptasi kembali meliputi; honeymoon, crisis, recovery dan adjustment. Fase adaptasi kembali berjalan secara efektif dengan menggunakan pendekatan psikologi komunikasi pada fase pemulihan (recovery).